Concurrent validity and accuracy of arm-wearable devices to detect heart rate during exercise: A systematic review - Nithiatthawanon, Teerawat; Chaikeeree, Nithinun; Boonsinsukh, Rumpa (Journal of Medicine and Health Sciences, 2023)
This study was systematically conducted to review research article regarding the accuracy and validity of commercial wearables in measuring heart rate during exercise. Studies published between 2014 - 2021 were searched in several databases, including ScienceDirect, PubMed, Scopus and the Web of science. Relevant studies with full text published in Thai and English were retrieved. The COSMIN and QUADAS were then used to assess the quality and risk of bias of each study. Later, data from selected studies were extracted, analyzed, and synthesized. The outcomes were divided into two categories (acceptable, unacceptable) and three (high, moderate, low) groups for accuracy and validity, respectively. There were 33 publications with Level 2, and based on the OCEBM examining 15 brands and 41 different arm-wearable devices. The data included studies illustrated that several arm-wearable devices were accurate (CCC = 0.86 - 0.96; MAPE < 5) and valid at a moderate to high level (r = 0.59 - 0.99) in measuring heart rate during both aerobic and resistance exercises. Thus, athletes, researchers, or those who were interested could apply this information on choosing a heart rate monitor for tracking heart rate while exercising. However, the study suggested that devices are consistently being developed and redesigned resulting in lower prices and using more accurate and valid technology, suggesting the need for more current reviews and further research.